2021
DOI: 10.1371/journal.pone.0252642
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation-induced alterations in maternal-fetal Heme Oxygenase (HO) are associated with sustained innate immune cell dysregulation in mouse offspring

Abstract: Heme oxygenase-1 (HO-1) is an evolutionarily conserved stress response enzyme and important in pregnancy maintenance, fetal and neonatal outcomes, and a variety of pathologic conditions. Here, we investigated the effects of an exposure to systemic inflammation late in gestation [embryonic day (E)15.5] on wild-type (Wt) and HO-1 heterozygous (Het, HO-1+/-) mothers, fetuses, and offspring. We show that alterations in fetal liver and spleen HO homeostasis during inflammation late in gestation can lead to a sustai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 53 publications
(112 reference statements)
0
6
0
Order By: Relevance
“…It has been found that parecoxib can attenuate the hepatic ischemia-reperfusion injury in rats by inhibiting the inflammation and oxidative stress 6 . Heme oxygenase-1 (HO-1) is an inducible heme oxygenase, and its activation is one of the most important cytoprotective mechanisms during cell stress 7 . Parecoxib can induce the HO-1 expression in macrophages and vascular smooth muscle cells through reactive oxygen species (ROS)-dependent pathway 8 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that parecoxib can attenuate the hepatic ischemia-reperfusion injury in rats by inhibiting the inflammation and oxidative stress 6 . Heme oxygenase-1 (HO-1) is an inducible heme oxygenase, and its activation is one of the most important cytoprotective mechanisms during cell stress 7 . Parecoxib can induce the HO-1 expression in macrophages and vascular smooth muscle cells through reactive oxygen species (ROS)-dependent pathway 8 .…”
Section: Introductionmentioning
confidence: 99%
“…At P60, brain and peripheral blood mononuclear cells (PBMCs) were collected from adult rats for flow cytometry consistent previous reports (17,(25)(26)(27)(28)(29)(30)(31). Using a Miltenyi adult brain dissociation kit and Miltenyi gentleMACS ™ protocol,…”
Section: Flow Cytometrymentioning
confidence: 97%
“…Using a separate panel, T cells were identified by assessing CD45 + CD3 + cells. CD45 + CD3 + CD4 + were classified as helper T cells and CD45 + CD3 + CD4 + CD25 + as regulatory T cells (Tregs) (22,23,29,30) (Figures 2A-G).…”
Section: Advances In Drug and Alcohol Researchmentioning
confidence: 99%
“…HO-1 plays a crucial role in heme degradation and cellular responses to stress [26]. During pregnancy, HO-1 maintains a balanced immune response and supports healthy placental development [27]. Evidence from a mouse model [27] indicates that it helps protect against oxidative stress and inflammation, which are often elevated in pregnancy-associated conditions.…”
Section: Discussionmentioning
confidence: 99%